Electro-separation of microalgal culture from wastewater. (November 2019) - Rafiee, Poorya; Tong, Yen Wah; Hosseini, Maryam; Ebrahimi, Sirous
Abstract: For further applications of microalgae such as bio-products, microalgal harvesting from its culture medium (e.g. wastewater) must be studied. This becomes more essential when investigating whether or not cells can stay viable to be recycled into the system. Microalgae culture, wastewater, and a mixture of both were separately electrocoagulated at wastewater Chemical Oxygen Demand ranging 66–2700 mg.l-1 and biomass dry weights between 1 and 8 g.l-1. The mixed culture contained species of C. Vulgaris, S. Obliquus, B. Braunii, B. Sudeticus, and A. Falcatus, since mixed culture technique can reduce the expenses in industrial scales by eliminating the costly sterilization strategies necessary to avoid contamination. The mixed samples were successfully separated with the efficiencies between 44-87% and 70–80% at different Chemical Oxygen Demand and biomass dry weights, respectively. In addition, it was shown that growth elements of carbon and nitrogen, although at lower rates, were consumed confirming the viability of the cells after electrocoagulation. The consumption rates for electrocoagulated samples were smaller than non-electrocoagulated samples only by 16, 12, and 31% in carbon, nitrate and ammonium concentrations, respectively. According to the obtained results electrical separation of microalgae could effectively harvest microalgae from wastewater without affecting the viability of the biomass. Highlights: Microalgal separation from wastewater was effectively carried out through electrocoagulation. Electrocoagulation displayed a potential technique for separation of microalgae without affecting the viability. Concentration of both wastewater and microalgae is a key in microalgae harvesting procedure. Removal of sterilization costs using mixed microalgae culture in wastewater treatment enhances the feasibility of scale-up.